Poems and Short Stories: Authentic Resources for English Language Learning - Yadav, Praveen Kumar (Journal of NELTA, 2015)
Maley, A., Mukundan J. & Widodo H. P. (2014). Poems and Short Stories: Authentic Resources for English Language Learning: LINCOM GmbH. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12090 Journal of NELTA, Vol 19 No. 1-2, December 2014: 169-171